Imię i nazwisko Jubilatki w przestrzeni historyczno-kulturowej i geograficznej - Rudnicka-Fira, Elżbieta (Poznańskie Spotkania Językoznawcze, 2014)
The article makes an attempt to characterize, possibly comprehensively, the selected personal names of the name Irena as well as the surnames Sarnowska and Giefing. Linguistic considerations, especially onomastic, are deeply rooted in the historical-cultural and geographical sphere, supported by a frequency factor.